1988
DOI: 10.6028/jres.093.151
|View full text |Cite
|
Sign up to set email alerts
|

Diffraction imaging (topography) with monochromatic synchrotron radiation

Abstract: Structural information of special interest to crystal growers and device physicists is now available from high resolution monochromatic synchrotron diffraction imaging (topography). In this review, the importance of superior resolution in momentum transfer and in space is described, and illustrations are taken from a variety of crystals: gallium arsenide, cadmium telluride, mercuric iodide, bismuth silicon oxide, and lithium niobate. The identification and detailed understanding of local variations in crystal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…[18][19][20] The resulting images map the incidence and distribution of structural anomalies and provide a basis for the determination of their nature. The images also provide a foundation for understanding and integrating the results of other characterization studies.…”
Section: A Essential X-ray Parameters and The Resulting Resolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20] The resulting images map the incidence and distribution of structural anomalies and provide a basis for the determination of their nature. The images also provide a foundation for understanding and integrating the results of other characterization studies.…”
Section: A Essential X-ray Parameters and The Resulting Resolutionmentioning
confidence: 99%
“…[18][19][20] The images were recorded on nuclear emulsion plates, which provide a spatial resolution of 1 m. They enable comprehensive interpretation of other structural observations obtained through etch- ing, ␥-ray diffraction, calorimetry, and resonance fluorescence spectroscopy. As a result, we are able to establish a structural model and develop an understanding of the sources of irregularity.…”
Section: A Essential X-ray Parameters and The Resulting Resolutionmentioning
confidence: 99%
“…Previous collaboration in high-resolution diffraction imaging of terrestrial mercuric iodide with Lodewijk van den Berg [7], who had grown this material himself in space, had verified the prominence in this material of individual grains, as reported following neutron and gamma-ray diffraction [25] and x-ray topography [12] [26]. A 2-6 µm cellular structure had also been reported [13].…”
Section: B Mercuric Iodidementioning
confidence: 72%
“…Unexplained cellular structure with a characteristic dimension of 2-6 µm has been observed in all mercuric iodide by scanning cathodoluminescence microscopy [13]. Previous exploratory high-resolution diffraction imaging of terrestrial mercuric iodide on the beam line [7] suggested that high-resolution imaging of additional crystals might prove to be extraordinarily interesting and fruitful in wrestling with these questions.…”
Section: Mercuric Iodidementioning
confidence: 99%
See 1 more Smart Citation